Type IV capitellum fractures in children. Issue 8 (4th August 2019) - Papamerkouriou, Yvonne-Mary; Tsoumpos, Pantelis; Tagaris, George; Christodoulou, George
Abstract : Capitellum fractures represent 1% of elbow fractures. A coronal shear fracture which involves the trochlea is classified as a type IV McKee fracture. The combination of its rarity in the paediatric population as well as its unique appearance on X-ray make diagnosis of this fracture a challenge. We present the case of a 14-year-old boy who sustained this fracture falling from his bike. It was diagnosed from the double arc sign on X-ray. In addition, a CT scan was obtained to aid preoperative planning. It was treated by open reduction and fixation with two headless compression screws. Follow-up at 6 months showed no avascular necrosis. The patient could achieve full extension, while flexion was reduced only by 5°. Final follow-up was conducted at 15 months. Anatomic reduction and stable internal fixation are essential for a good outcome in these uncommon paediatric fractures.